2012
DOI: 10.5860/rusq.51n3.278
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on E-books from Instructors and Students in the Social Sciences

Abstract: Perspectives on E-books from instructors and students in the social sciences volume 51, issue 3 | Spring 2012 279Perspectives on E-books from Instructors and Students in the Social Sciences

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 15 publications
4
12
0
Order By: Relevance
“…But like any other technological innovation in education, with continued usage, students are likely to gradually get more familiar and confident in using textbooks in digital formats. Hoseth and Merinda (2012) in their paper similarly concluded that participants in their study clearly expressed the need to adapt to change and switch to digital textbook formats, and successively becoming more familiar with them over time. This is in consonance with Chou (2014: p. 16) when he concludes that, "When students are given time and opportunities to read e-books, they are likely to develop e-book reading habits.…”
Section: Discussionmentioning
confidence: 84%
“…But like any other technological innovation in education, with continued usage, students are likely to gradually get more familiar and confident in using textbooks in digital formats. Hoseth and Merinda (2012) in their paper similarly concluded that participants in their study clearly expressed the need to adapt to change and switch to digital textbook formats, and successively becoming more familiar with them over time. This is in consonance with Chou (2014: p. 16) when he concludes that, "When students are given time and opportunities to read e-books, they are likely to develop e-book reading habits.…”
Section: Discussionmentioning
confidence: 84%
“…Participants’ feedback served as data to inform future cellphone library services (Paterson and Low, 2011). Similar studies that applied focus groups to examine technology uses have been reported by Seeholzer and Salem (2011) and Hoseth and McClure (2012). One of the studies on IPAs cited earlier (Cowan et al, 2017) applied the focus group method to investigate infrequent IPA users’ views, practices, and barriers to use of IPA technology.…”
Section: Methodsmentioning
confidence: 85%
“…It is widely used in market research, branding, and new product development contexts (Greenbaum, 2000) and has a long history in the social sciences (Wilkinson, 2010). Within information disciplines, it is frequently used for studying user behavior, expectations, and preferences related to information technology (Hoseth and McClure, 2012; Seeholzer and Salem, 2011), as well as for new product development (Paterson and Low, 2011). For example, one of the frequently cited recent studies of technology adoption used focus groups to investigate students’ use of cellphones at the University of Edinburgh (Paterson and Low, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…14 Perhaps related to this, faculty and graduate student ebook users in another study characterized their engagement with ebooks as less intellectual. 15 Instructor support may mitigate negative student perceptions about ebooks. A study of undergraduates found that allowing students to choose whether or not to use an ebook can actually encourage them to try an ebook.…”
Section: Literature Reviewmentioning
confidence: 99%